The maintenance care of potential organ donors: ethnographic study on the experience of a nursing team (Revista Latino-Americana de Enfermagem, 2007)
This ethnographic study aimed to understand a nursing team's experience on the maintenance of potential organ donors. Data were collected through ethnographic interview, participative observation and documental analysis and analyzed in thematic, cultural domain and taxonomical terms. The research enabled us to identify the meaning of brain death, revealing the interrelation between the categories (units, nursing team and patient), which constituted this study main theme: "it is not a person". The transplant meaning held by the nursing team is marked by disbelief due to some previous experiences in the Intensive Therapy Unit. Thus, beliefs and values of this subculture interfere or determine a distancing from the patient with a consequent loss in the maintenance of the potential donor and quality of the organs donated.